Florian Krobb: „Afrikas Zukunft“. Jugend- und Abenteurliteratur in Deutschlands „afrikanischem Jahrhundert“ (1840-1940) - Jagdschian, Larissa Carolin

Das Gedächtnis des Bilderbuchs – Postmemoriale Perspektiven auf die Verfolgung im Dritten Reich in intergenerationalen Bilderbüchern - Jagdschian, Larissa Carolin (Begegnungen von Jung und Alt in der Kinder- und Jugendliteratur. Literaturwissenschaftliche und literaturdidaktische Perspektiven)

Politische Bildung mit Jugendromanen über Flucht, Rassismus und Solidarität im Deutschunterricht. - Jagdschian, Larissa Carolin (Politische und Ästhetische Bildung im Deutschunterricht. Kinder- und Jugendmedien aus der Perspektive einer Politischen Literatur- und Mediendidaktik)

Julya Rabinowich: Dazwischen: Ich (2016) - Ein Adoleszenzroman über interkulturelle Identitätsprozesse. - Jagdschian, Larissa Carolin (Interkulturalität neu entdecken: fachwissenschaftliche und fachdidaktische Perspektiven auf Kinder- und Jugendliteratur)

Travelling memories. Deutschsprachige Kinder- und Jugendliteratur über die Flucht während des Na-tionalsozialismus und aus der DDR - Jagdschian, Larissa Carolin

Diachrone Perspektiven auf die deutschsprachige Kinder- und Jugendliteratur über die Verfolgung während des Nationalsozialismus - Jagdschian, Larissa Carolin (kjl&m)

Medizinische Schreibweisen in der enzyklopädischen Literatur für Kinder im 18. und 19. Jahrhundert. - Jagdschian, Larissa Carolin (kjl&m)

Schriftgestaltung und Schriftästhetik im Bilderbuch. Typographisch-ästhetische Deutungen von Grundschulkindern - Härtel, Kira; Drepper, Laura; Topalovic, Elvira (kjl&m, Texte sichtbar machen. Schrift und Schriftkultur in der Kinder- und Jugendliteratur)

Une nouvelle grammaire universitaire du français à l’intention des étudiants allophones : la Grammatik des gesprochenen und geschriebenen Französisch (zs. mit Dirk Siepmann) - Bürgel, Christoph (Actes du Congrès Mondial de Linguistique française 2024 - 9ème Congrès Mondial de Linguistique Française)

Ars est celare artes. Zur Rocca di Tristano-Episode in Ariostos Orlando furioso - Steigerwald, Jörn (Rhetorik)

Einleitung - Steigerwald, Jörn; Hetzel, Andreas (Rhetorik)

Sustainable rural electrification through community-managed mini-grids: Evidence from Tanzania - Ngoti, Irene Fredolin

Methodische Einführung des Konzeptes Messunsicheheiten in der Physik - Sprachliche Analyse von Standardwerken - Bauer, Anna Brigitte (Wissenschaftsdidaktik als kritische Kommunikationsanalyse - Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Do Organizations Utilize Social Media Affordances? A Qualitative Investigation of Social Media Management Activities - Arslan, Kader; Trier, Matthias (Proceedings of the 19th International Conference on Wirtschaftsinformatik (WI 2024))

UPB-NT submission to DCASE24: Dataset pruning for targeted knowledge distillation - Werning, Alexander; Haeb-Umbach, Reinhold

Soft Sensor Model of Phase Transformation During Flow Forming of Metastable Austenitic Steel AISI 304L - Rozo Vasquez, Julian; Kersting, Lukas; Arian, Bahman; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Lecture Notes in Mechanical Engineering)
This paper deals with the modeling of a soft sensor for detecting α’-martensite evolution from the micromagnetic signals that are measured during the reverse flow forming of metastable AISI 304L austenitic steel. This model can be prospectively used inside a closed-loop property-controlled flow forming process. To achieve this, optimization by means of a non-linear regression of experimental data was carried out. To collect the experimental data, specimens were produced by flow forming seamless tubes at room temperature. Using a combination of production parameters (like the infeed depth and feed rate), specimens with different α’-martensite contents and wall-thickness reductions were produced. An equation to compute α’-martensite from both specific production-process parameters and micromagnetic Barkhausen noise (MBN) measurements was obtained using numerical methods. In this process, the behavior of the quantity of interest (namely, the α’-martensite content) was mathematically evaluated with respect to non-destructive MBN data and the feed rate that was used to produce the components. A combination of exponential and potential functions was defined as the ansatz functions of the model. The obtained model was validated online and offline during the real flow forming of workpieces, obtaining average deviations of up to 7% α’-martensite with respect to the model. The implementation of the soft sensor model for property-controlled production represents an important milestone for producing high-added-value components on the basis of a well-understood process-microstructure-property relationship.

Barkhausen noise- and eddy current-based measurements for online detection of deformation-induced martensite during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank
This paper deals with micromagnetic measurements for online detection of strain-induced α’-martensite during plastic deformation of metastable austenitic steel AISI 304L. The operating principles of the sensors are Barkhausen noise (MBN) and eddy currents (EC), which are suitable for detection of microstructure evolution due to formation of ferromagnetic phases. Nevertheless, the description of the calibration and transformation models of the micromagnetic measurements into quantitative α’-martensite fractions is beyond the scope of this paper. The focus will be put on the qualification of different micromagnetic methods as well as of different measurement systems under conditions similar to the real ones during production, which is crucial for implementation of a property-controlled flow forming process. The investigation was carried out on tubular specimens produced by flow forming, which have different content of α’-martensite. To characterize the sensitivity of the sensors, different contact conditions between sensors and workpieces were reproduced. MBN sensors are suitable for detecting amount of α’-martensite, but the measurements are affected by the surface roughness. This entails that the calibration models for MBN sensors must take account of these effects. EC sensors show a closer match with the amount of α’-martensite without having major affectation by other effects.

Innovative measurement system for saber curvature observation in straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Procedia Computer Science)

Batch constrained multi-objective Bayesian optimization using the example of ultrasonic wire bonding - Reiling, Fabian; Henke, Christian; Hunstig, Matthias; Gröger, Stefan; Trächtler, Ansgar (2024 IEEE International Conference on Advanced Intelligent Mechatronics (AIM))

A comprehensive test infrastructure for the evaluation of energy management systems of the household and grid level - Stieren, Stephan; Werner, Achim; Henke, Christian; Trächtler, Ansgar (2024 IEEE Conference on Technologies for Sustainability (SusTech))